Lactate and catecholamines: a physiological response in critically ill patients - Torres-Cabezas, Pedro (2022)
Lactate is a highly dynamic metabolite that is produced, under anaerobic conditions, due to hypoxia or ischemia. Under aerobic conditions, it is synthesized by a mechanism driven by the stimulation of the β2 adrenergic receptor, which increases the activity of the sodium-potassium pump, and by a state of accelerated aerobic glycolysis. This metabolite is capable of being exchanged between different producing and consuming cells, ensuring the raw material for energy production.The sympathetic nervous system responds to stress stimuli through the release of catecholamines, which act as hormones and neurotransmitters in various tissues of the body, allowing an increase in metabolism that raises glucose and available oxygen levels.There is a physiological dependence between catecholamine levels and lactate production, predisposing the body to respond effectively to a stressful situation. However, an exacerbated adrenergic response may cause exaggerated effects on sensitive tissues that increase the probability of failure. Based on the knowledge of these mechanisms, therapeutic strategies focused on regulating the sympathetic activity are proposed.